Marketing the outdoors: a systematic review of hiking, nature-based tourism, and visitor analytics - Desy Oktaviani; Yolanda Masnita; Husna Leila Yusran (Indonesian Institute For Counseling, Education and Therapy, 2026)
Outdoor and nature-based tourism has experienced rapid growth, accompanied by increasing scholarly interest in understanding how these experiences can be effectively marketed while promoting sustainability and visitor well-being. This systematic literature review synthesises findings from four thematic domains: (1) conceptual foundations and destination positioning; (2) psychological drivers and behavioral outcomes; (3) technology-enhanced visitor analytics; and (4) sustainability, ethics, and future directions. Drawing on empirical evidence from studies employing surveys, experiments, neuromarketing, GPS tracking, VR, topic modelling, and visual analytics, the review reveals that outdoor tourism behavior is shaped by experiential authenticity, emotional and cognitive engagement, identity formation, and social dynamics. Technological innovations provide powerful tools for understanding visitor behavior but raise significant ethical considerations related to privacy and transparency. Sustainability emerges as a central dimension, with experiential value and place attachment shown to promote environmentally responsible behavior. The review concludes by proposing the need for integrated theoretical frameworks, interdisciplinary methodological advances, ethical data governance, and community-centred approaches to ensure that outdoor tourism marketing is both impactful and sustainable.